The Anb Angle Value In Adults Wıth Normal Occlusıon - Emel Seren (Turkish Journal of Orthodontics, 1990)

(untitled)
The aim of this research was to find the mean value of ANB angle, standart deviation and the differences between sexes was conducted on 85 individuals (48 male, 37 females) aged 18-20 with normal occlusion by using standart cephalometric x rays. The mean value of ANB angle in females was 2.9 ± 2.2, in males: 2.5 ± 2.3 degrees. The difference between sexes was found insignificant.